Transformasi Pemasaran Di Era Digital: Optimalisasi Landing Page Untuk Meningkatkan Brand Awareness Pada Jasa Pengepul Sampah-Karung Sampah - Erica Trisnawati; R. Yuniardi Rusdianto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Business transformation in the digital era requires an innovative marketing approach. One way is by utilizing the potential of the internet and information technology. This research focuses on the important role of landing pages in designing online experiences for consumers. The theoretical basis involves the concept of marketing transformation, landing page optimization, and the importance of brand awareness for waste collection services. The methodology used adopts a qualitative approach with a case study in Karung Sampah. Data is collected through observation and analysis using third parties, namely Google Search Console and Google Analytics. It was found that responsive design, relevant content, and social media integration played an important role in the success of the campaign (brand awareness)